PENGEMBANGAN MEDIA LUMI (LUDO EKONOMI) PADA MATA PELAJARAN IPAS MATERI KONDISI PEREKONOMIAN DAERAH KELAS V DI MIN 2 MALANG. SUMBERMANJING WETAN - Tirtoadji, Yahya Lucky (Ibtidaiyyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
ABSTRACT The objectives of this development research include explaining media development procedures, knowing the level of media validity, and media attractiveness so that it is expected to help the learning process of grade V MIN 2 Malang students, Sumbermanjing Wetan in understanding the material of regional economic conditions in Indonesia. This research uses the type of research and development I (R &D) by applying the Borg and Gall model or approach 10 stages which have been modified into 6 stages including (1) Data collection, (2) Design planning, (3) Initial product design, (4) Initial product trials, (5) Initial product revisions, and (6) Main field tests. The subjects of this study were 24 students of grade V MIN 2 Malang, Sumbermanjing Wetan. This research data collection technique includes observation, interviews, questionnaires, and documentation. The data results were analyzed using qualitative and quantitative data analysis techniques. The results of this research are in the form of LUMI (Ludo Ekonomi) learning media products which are included in the conventional media category. The results of the validation of learning media products get a score of 96% or in the very decent category, while the value of learning materials gets a value of 90% with the very decent category, and the validation of learning media experts gets a value of 94% which is also included in the very decent category. In addition to the validation results, there were student response results obtained from the results of the questionnaire with a value of 88.41% or included in the very positive category. Based on the results of validation and the results of field trials, it can be concluded that the LUMI (Ludo Ekonomi) learning media which contains material on regional economic conditions is very feasible and very positive to be used as a science learning media in class V MIN 2 Malang, Sumbermanjing Wetan. ABSTRAK Tujuan penelitian pengembangan ini antara lain menjelaskan prosedur pengembangan media, mengetahui tingkat kevalidan media, dan kemenarikan media sehingga diharapkan dapat membantu proses belajar siswa kelas V MIN 2 Malang, Sumbermanjing Wetan dalam memahami materi kondisi perekonomian daerah di Indonesia. Penelitian ini menggunakan jenis penelitian research and developmentI (R&D) dengan menerapkan model atau pendekatan Borg and Gall 10 tahapan yang telah di modifikasi menjadi 6 tahapan meliputi (1) Pengumpulan data, (2) Perencanaan desain, (3) Desain produk awal, (4) Uji coba produk awal, (5) Revisi produk awal, dan (6) Uji lapangan utama. Subjek penelitian ini adalah 24 siswa kelas V MIN 2 Malang, Sumbermanjing Wetan. Teknik pengumpulan data penelitian ini meliputi observasi, wawancara, angket, dan dokumentasi. Hasil data dianalisis menggunakan teknik analisis data kualitatif dan kuantitatif. Hasil dari penelitian ini berupa produk media pembelajaran LUMI (Ludo Ekonomi) yang masuk dalam kategori media konvensional. Adapun hasil validasi produk media pembelajaran mendapat nilai 96% atau dalam kategori sangat layak, sedangkan nilai materi pembelajaran mendapatkan nilai 90% dengan kategori sangat layak, dan validasi ahli media pembelajaran mendapatkan nilai sebesar 94% yang juga termasuk dalam kategori sangat layak. Selain hasil validasi, terdapat hasil respon siswa yang diperoleh dari hasil angket dengan nilai sebesar 88,41% atau masuk dalam kategori sangat positif. Berdasarkan hasil validasi dan hasil uji coba di lapangan, maka dapat disimpulkan bahwa media pembelajaran LUMI (Ludo Ekonomi) yang berisi materi kondisi perekonomian daerah ini sangat layak dan sangat positif untuk dijadikan media pembelajaran IPAS di kelas V MIN 2 Malang, Sumbermanjing Wetan.